Bienfait: The Saskatchewan Miners' Struggles of '31 - Dishaw, Garnet (Briarpatch, 2003)
Brief review of: "Bienfait" by Stephen Endicott.
Keywords: Coal industry; Coal mines; History; Labor unions; Political Science; Strikes